AKTIVITAS INTERAKSI PARA SOCIAL MENINGKATKAN PERFORMA INFLUENCER DALAM MEMPENGARUHI MINAT PEMBELIAN PRODUK FASHION MUSLIMAH (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS WAHID HASYIM SEMARANG) - Elya Septi Widya Ningrum; Cici Herlina Putri; Fiki Syakhiyah Sa'adah; Putri Faizah; Ratih Pratiwi (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2022)
This study aims to determine the effect of parasocial interaction variables on influencers, parasocial interaction variables on buying interest, influencer variables on buying interest, and parasocial interaction variables on buying interest through influencers on students of the economics faculty of Wahid Hasyim University, Semarang who have purchased Muslim clothing. This research method is quantitative. The population in this study amounted to 1,128 students. The number of samples is 130 students using the sample size according to the opinion of Heir, et al. This study uses statistical analysis which is used to determine the direct and indirect relationship between parasocial interaction variables, influencer variables and buying interest variables. The results obtained that parasocial interaction variables directly affect influencers, parasocial interaction variables directly affect buying interest, Influencer variables directly affect buying interest, and parasocial interaction variables directly affect buying interest through influencers.